2014
DOI: 10.1136/bcr-2014-205832
|View full text |Cite
|
Sign up to set email alerts
|

Kikuchi-Fujimoto disease presenting after consumption of ‘Miracle Mineral Solution’ (sodium chlorite)

Abstract: We present a case report of a 41-year-old woman of Malay ethnicity who presented with an 11-day history of fever and left-sided lymphadenopathy after consuming ‘Miracle Mineral Solution’ (sodium chlorite solution) for the first time. A diagnosis of Kikuchi-Fujimoto disease was established via lymph node biopsy after other differentials were excluded. The aetiology of Kikuchi-Fujimoto disease remains controversial, but viral, autoimmune and physicochemical causes have been suggested as possibilities. In this ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 8 publications
(10 reference statements)
0
9
0
4
Order By: Relevance
“… 200 Another case report indicated that a 41-year-old woman developed Kikuchi-Fujimoto disease (KFD) 201 after consuming MMS, which resulted in fever spiked to 40°C, chills, tachycardia, rigors, and dry cough. 202 She recovered after 16 days of treatment for her symptoms and continuous follow-up. 202 The use of these unproven chemicals is dangerous, and extreme caution needs to be implemented.…”
Section: Unproven Chemicalsmentioning
confidence: 94%
See 2 more Smart Citations
“… 200 Another case report indicated that a 41-year-old woman developed Kikuchi-Fujimoto disease (KFD) 201 after consuming MMS, which resulted in fever spiked to 40°C, chills, tachycardia, rigors, and dry cough. 202 She recovered after 16 days of treatment for her symptoms and continuous follow-up. 202 The use of these unproven chemicals is dangerous, and extreme caution needs to be implemented.…”
Section: Unproven Chemicalsmentioning
confidence: 94%
“… 202 She recovered after 16 days of treatment for her symptoms and continuous follow-up. 202 The use of these unproven chemicals is dangerous, and extreme caution needs to be implemented. 203 …”
Section: Unproven Chemicalsmentioning
confidence: 94%
See 1 more Smart Citation
“…• Más publicaciones técnicas/reportes médicos de casos parecidos son ampliamente encontrados (Nguyen et al, 2014;Loh y Shafi, 2014;Moore y Calabrese, 1980b;Williams et al, 2009;Arnold y Rushton, 2018;Moore et al, 1978;Patat, 2011;Brocker et al, 2011;Nicolas et al, 2016 Defensores del MMS no son ajenos a la existencia de varios síntomas relacionados a su utilización y parecen tener la tendencia a explicarlos mediante la reacción Jarisch-Herxheimer (Dhakal y Sbar, 2020;Butler, 2017). Según la explicación que brindan en sus libros y foros (Jim y Lloyd, 1998;Oswald, 2020;Kalcker, 2017;Rivera, 2013), estos síntomas pueden ocurrir después de la ingestión del MMS como parte de un "proceso de desintoxicación producido por la liberación de toxinas de patógenos y parásitos que deben primero ser expulsados por el cuerpo".…”
Section: Documentación Científica Sobre La Toxicidad Asociada a La Utilización Del Mms Y Otrosunclassified
“…According to the Food and Drug Administration (FDA) of the US, consuming ClO 2 can lead to adverse effects such as ‘vomiting, diarrhoea, dehydration, abdominal pain, metahemaglobinemia and systemic failures that could potentially lead to death’. However, an impartial review of the scientific peer-reviewed literature reveals few case reports of human patients presenting adverse effects after consumption of ClO 2 , none of which were fatal, and reversed completely after treatment [6–9]. Published studies on ClO 2 toxicity have reported null to mild effects in adult humans and other animals [1012] and have stressed that toxicity is strongly dose-dependent [1214].…”
Section: Introductionmentioning
confidence: 99%